STATISTIK : SALAH SATU INDIKATOR UTAMA PERADABAN - Maman A. Djauhari (Jurnal Sosioteknologi, 2007)
Todays statistics has appeared as universal language in the modern communication in Indonesia. It has been a need of civilization such as reading and writing, and also as a civilization indicator of a nation. This paper offers an idea that views statistics as a soft technology that is able to bring this nation to the more civilized nation. An example is presented as the illustration.